Evaluation of the Primary Care Network in the city of Recife-PE from the perspective of a group of users: Evaluación de la Atención Primaria de Salud - Gabriela Mota de Freitas, Carolina; Lisboa da Silva, Thaís Carine; de Paula Carneiro Porto Gomes, Neciula (Journal of Health Care, 2021)
Introduction: Primary Health Care has become the main gateway and first contact the user has with the health care networks, being fundamental its accomplishment among cities to improve the Brazilian Health System. In this context, it is necessary to identify the real applicability of the health service model, along with its limitations, considering the perception of users as an important tool for evaluating these services. Objective: To evaluate the attributes of primary health care in Recife-PE from the perspective of users. Materials and Methods: Observational, analytical-descriptive, cross-sectional study. Participants were 80 adult registered users in the Health Units of Recife. The Primary Care Assessment Tool - adult users, reduced version was applied. Results: The components Degree of Affiliation, First Contact Access - Utilizationand Coordination - Integration of care - reached average scores above 6.6, being well evaluated. The dimension First Contact Access - access to care - obtained scores below 6.6, not reaching the desirable established average, not allowing the full reach of the First Contact Access attribute. Regarding the relationship between the assessment of attributes and sociodemographic variables, there was only a correlation between the age group and the first contact access - utilization. Conclusions: Although users have been recognizing the Primary Care Health Centers as the main health care resource and value it as a care coordinator, still remain difficulties in the access to care into the health service, being necessary new strategies that make possible an increase in the access to the health care system.